N‐SnOx as a Transparent Electrode and Heterojunction for p‐InP Nanowire Light Emitting Diodes. Issue 11 (7th April 2022) - Gagrani, Nikita; Vora, Kaushal; Adhikari, Sonachand; Jiang, Yuxin; Jagadish, Chennupati; Tan, Hark Hoe
Abstract: Transparent electronics are rapidly evolving with the development of transparent conducting oxides (TCOs). This work investigates both the electrical and optical properties of n‐type tin oxide (SnO x ) film, deposited at various levels of oxygen concentration using magnetron sputtering. The band alignment at InP–SnO x interface is further studied and SnO x deposited at various conditions is used to demonstrate InP nanowire (NW) light emitting diodes (LEDs) to understand the trade‐off between absorption and resistance. It is found that the device with lower resistance but higher absorption outperforms in terms of output power. Emission from the devices consists of two peaks at room temperature due to conduction band‐to‐heavy hole band transition and conduction band‐to‐light hole band transition. Decreasing the operating temperature brings about quite a complex transition in all the devices, which consists of two additional peaks due to Zn acceptor level and zincblende/wurtzite (ZB/WZ) recombination at NW/substrate interface. At temperatures below 208 K, the emission peak from conduction band‐to‐light hole band transition quenches, however the emission peaks from Zn acceptor level and ZB/WZ recombination become prominent. This work lays the foundation for realizing a new generation of efficient transparent electrodes in conjunction with NWs, eliminating the complex epitaxial growth process optimization of NW shell growth, heterostructure and doping. Abstract : Owing to higher conductivity and lower absorption, transparent conducting oxides (TCOs) are becoming popular as transparent electrodes. However, a trade‐off between absorption and resistance exists. In this work, tin oxide, a commonly used TCO, is investigated as both dopant and electrode layer. The balance between absorption and resistance is also demonstrated by fabricating p‐InP/n‐SnO x nanowire light‐emitting diodes.